Ultimate Swift programming (O'Reilly Media, 2015)
"Building apps for iPhone, iPad, and Mac just got easier, faster, and safer, now that Apple has released Swift. In this video workshop, Secret Lab co-founders Jon Manning and Paris Buttfield-Addison, together with Tim Nugent, take you through the components used for building iOS and OS X apps with Swift, and then step through the creation of a simple notepad from scratch, with counterparts for each operating system. If you're an experienced programmer who's never touched Apple developer tools before, you'll learn the basics for putting the Swift language, the Xcode IDE, Interface Builder, and many other Apple technologies to work. With this video workshop, you'll learn how to turn your app ideas into reality."--Resource description page.